Enhanced oxygen electrocatalysis in zinc-air batteries via a bifunctional bimetallic organic framework - Shivade, Rajkiran D.; Pandey, Priyanshi; Shelke, Manjusha V. (Journal of Power Sources, 2025)
An efficient bifunctional oxygen electrocatalyst, a nickel-iron metal organic framework (NF-MOF) grown within three-dimensional (3D) nitrogen doped porous carbon (NPC) collectively referred as NF-MOF@NPC, is developed as high performance electrocatalyst for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The synergistic effect of bimetallic active sites coupled with conductive nitrogen doped porous carbon matrix, provides chemical stability, abundant active sites, enhanced electron transfer, and improve catalytic activity. NFMOF@NPC exhibits OER onset potential of 1.60 V at current density of 10 mA cm- 2 with Tafel slope of 126 mV dec- 1 and ORR half wave potential of 0.81 V with electron transfer number of 3.91. A zinc-air battery fabricated using NF-MOF@NPC shows peak power density of 102 mW cm-2 and specific capacity of 741 mAh g-Z 1n. It also exhibits remarkable cycling stability for 120 h at current density of 10 mA cm- 2 highlighting its promise as alternative for conventional platinum on carbon (Pt/C) and ruthenium dioxide (RuO2) electrocatalysts demonstrating its potential for next generation energy storage devices.
Keywords: Bifunctional Electrocatalyst; Rotating disk electrode; zinc-air battery